Raptor selection of captive reared and released Galliform birds - Rebecca Perkins; Clint W. Boal; C. Brad Dabbert (Wildlife Society Bulletin)
ABSTRACT Captive rearing and release of birds in the order Galliformes remains a popular management tactic despite low survival rates. We investigated avian predator selection of captive‐reared northern bobwhites (Colinus virginianus) as a potential driver of their high mortality. We simulated avian predator hunts on a flushing pair of bobwhites during trials conducted from 6 February 2015 to 14 February 2015 in Texas, USA. When presented a choice of a captive‐reared bobwhite or wild bobwhite, a Harris's hawk (Parabuteo unicinctus) pursued a captive‐reared bobwhite in 8 of 10 flight trials. This selective rate, combined with observations from auxiliary research indicate avian predation may be a greater risk for captive‐reared birds than wild birds. The success of captive‐rearing and release efforts may benefit from a better understanding of how to more adequately prepare captive‐reared birds for release. © 2018 The Wildlife Society.